المعلم الفعال و طرق إعداده في الفكر التربوي الحديث - رميتة طارق (University of Eloued جامعة الوادي, 2024)
يعتبر المعلم العنصر المهم في العملية التعليمية وأساسها، كيف لا وهو من يحمل على عاتقه مهنة شاقة يقاس من خلالها مدى نجاح السياسة التعليمية. وهو بذلك يتحمل جزء كبير من هذا النجاح أو الفشل ولتسليط الضوء على هذه الجزئية، فقد تطرقنا في بحثنا هذا إلى عدة عناصر مرتبطة بالمعلم و أدائه التربوي منها: الآليات المعتمدة في اختيار معلمي المستقبل، إضافة إلى التطرق إلى ضرورة مراعاة واقع المعلم الذي يعيشه وظروفه الاجتماعية والاقتصادية، وكدا التطرق إلى صفات المعلم الفعال ، الذي يرجى منه تحقيق أهداف السياسات التعليمية دون أن نغفل في هذا البحث ضرورة الاهتمام بتكوين المعلم بشقيه التكوين العلمي والأكاديمي وضرورة تكوينه على الاستعمال الأمثل للوسائل التقنية الحديثة خاصة في ضوء التطور العلمي السريع الذي تشهده المجتمعات ، إضافة إلى المرور على مميزات المعلم الجيد و المبادئ الأساسية لإعداد المعلم في طرح علمي وجيز. Abstract: The teacher is considered the most important element in the educational process and its basis. Why not, and he is the one who carries on his shoulders a difficult profession through which the success of the educational policy is measured. Thus, he bears a large part of this success or failure. To shed light on this part, we have touched in this research on several elements related to the teacher and his educational performance, including: The mechanisms adopted in the selection of future teachers, in addition to addressing the need to take into account the reality of the teacher in which he lives and his social and economic conditions, as well as addressing the qualities of an effective teacher, who is expected to achieve the objectives of educational policies without overlooking in this research the need to pay attention to the formation of the teacher in both parts of the scientific and academic formation and the necessity Training him on the optimal use of modern technical means, especially in light of the rapid scientific development witnessed by societies, in addition to passing on the characteristics of a good teacher and the basic principles of teacher preparation in a brief scientific presentation
Keywords: المعلم; الفعال; الإعداد; preparation; effective; Teacher